Frogs - Bishop, Nic, 1955- (New York : Scholastic Nonfiction, 2008)
Nic Bishop's photographs show all different kinds of frogs, big ones, very tiny ones, frogs with beautiful colors of skin, and one frog you can see inside of.
Includes index.
A Junior Library Guild selection
Keywords: Frogs -- Juvenile literature; Frogs